2020
DOI: 10.3390/met10101299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasound on Pore and Crack Formation in Laser Beam Welding of Nickel-Base Alloy Round Bars

Abstract: Welding by laser beam is a method for creating deep and narrow welds with low influence on the surrounding material. Nevertheless, the microstructure and mechanical properties change, and highly alloyed materials are prone to segregation. A new promising approach for minimizing segregation and its effects like hot cracks is introducing ultrasonic excitation into the specimen. The following investigations are about the effects of different ultrasonic amplitudes (2/4/6 µm) and different positions of the weld poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The distance to each other and to the specimen is 50 mm aiming above the specimen to reduce the keyhole's gas plume and at the specimen bottom for cooling and melt drop prevention since the gas jet fans out. The general parameters have been determined by previous investigations [22][23][24] at 8 kW average welding power and 0.95 m/min welding speed.…”
Section: Methodsmentioning
confidence: 99%
“…The distance to each other and to the specimen is 50 mm aiming above the specimen to reduce the keyhole's gas plume and at the specimen bottom for cooling and melt drop prevention since the gas jet fans out. The general parameters have been determined by previous investigations [22][23][24] at 8 kW average welding power and 0.95 m/min welding speed.…”
Section: Methodsmentioning
confidence: 99%
“…Lei et al [16] suggested that the porosity at the weld seam is greatly improved by the cavitation and acoustic streaming of the ultrasonic vibration on the weld pool in ultrasound-assisted laser welding of AZ31B magnesium alloy. Grajczak et al [21] found that porosity can be eliminated when the weld pool is located in the antinode position during ultrasound-assisted laser welding of nickel-based-alloy round bars. He and Shen [17] analyzed the effects of different welding positions on porosity in laser welding of aluminum alloys and observed the minimal porosities in vertical down welding, with high stability of the keyhole.…”
Section: Introductionmentioning
confidence: 99%